Improving Students’ HOTs-Literacy Abilities Through Making Summaries at The End of Learning - Iis Siti Jahro; Ani Sutiani; Suryani Suryani; Asep Wahyu Nugraha (Universitas Negeri Medan, 2024)
The reading and writing habits of SMAN 2 Percut Sei Tuan students are relatively low. Therefore, students' literacy and high order thinking abilities are also relatively low. The implementation of scientific literacy-based learning strategies in the form of making summaries at the end of the learning process is expected to improve students' literacy and high order thinking skills. The instruments used are tests in the form of varied multiple choices and essays totaling 8 and 2 questions. The results of data analysis show that students' initial abilities on the 9 of HOTs-Literacy indicators are very low with an average value of 28.49. The summarizing treatment at the end of the learning process succeeded in improving the ability of HOTs-Literacy students in indicators (1) identifying information and data, (2) using information and data, (3) producing explanatory models, (4) distinguishing questions that can be researched scientifically, (5) formulating hypotheses, (6) making predictions, (7) analyzing data, (8) interpreting data, (9) drawing or presenting conclusions, respectively 63.7 ; 66.7; 68.4 ; 64.0 ; 70.9 ; 70.8; 79.2 ; 81.4 and 86.3 %.